Serenity – A Manifestation of Overcoming Discouragement, Despair and Nihilism: The Legacy of Father Francis Blachnicki - Żywczok, Alicja (Paedagogia Christiana, 2024)
This article offers a biographical reconstruction and interpretation of a part of Father Francis Blachnicki’s legacy, focusing on felicitological issues, particularly the concept of serenity. The article’s structure is designed to present the research findings effectively. The initial section clarifies basic concepts, outlines methodological assumptions and portrays Father Blachnicki as a cheerful individual to contextualise biographical facts within a broader framework. Subsequently, his interpretation of serenity and the methods for achieving it, including an appropriate educational process, are explained. The antonyms of serenity, such as sadness, despondency, defeatism and despair, as found in Blachnicki’s work, are identified and described. This narrative is enriched with ethical, social and educational suggestions from Blachnicki and directed towards contemporary audiences. His legacy represents an original and inspiring spiritual exploration, underscoring the importance of ensuring that its teachings and message are comprehended accurately by future generations.